Androgen Stimulation of PCA3 and miR-141 and Their Release from Prostate Cancer Cells - Gezer, Ugur (Cell J, 2015)
OBJECTIVE: Prostate cancer antigen 3 (PCA3) and microRNA-141 (miR-141) are emerging molecules in prostate cancer (PCa) pathogenesis and have been shown to be involved in androgen signaling. In this original research, we designed an experimental cell model with androgen-sensitive LNCaP cells to comparatively assess the extent of androgen responsiveness of PCA3-mRNA and miR-141 along with prostate specific antigen (PSA)mRNA and their release into culture medium. These molecules were also measured in the plasma of the patients with early PCa which is considered to be analogous to androgenresponsive cells. MATERIALS AND METHODS: In this experimental study, LNCaP cells were exposed to androgen ablation for 48 hours and treated then with dihydrotestosterone (DHT) for 24 hours. Expression of all three RNA molecules in cells, culture medium or plasma was measured by quantitative polymerase chain reaction (qPCR). RESULTS: Our results show that DHT differentially affects the expression of these molecules. PCA3 was the most evidently induced molecule (up to 400-fold, p<0.001), while the effect was moderate for PSA-mRNA (up to 30-fold, p<0.001). In contrast, the stimulation of miR-141 was much weaker (up to 1.5-fold, p>0.05). With regard to the release into culture medium, a similar picture was observed except for PCA3. PCA3 was below the detection level despite its high stimulation. DHT treatment led to a significant release of PSA-mRNA (up to 12-fold). Similar to its induction pattern in LNCaP cells, miR-141 was released at a limited quantity into the medium (up to 1.7- fold, p=0.07). In plasma, only PCA3 differed significantly between the patients and healthy subjects (p=0.001). CONCLUSION: Our findings indicate that PCa-related RNA molecules respond differentially to androgen stimulation suggesting differential regulation by androgens.